2019
DOI: 10.3390/ijerph16173118
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Daily Simulation of Mountain Flood Processes Based on the Modified Soil Water Assessment Tool (SWAT) Model

Abstract: Floods not only provide a large amount of water resources, but they also cause serious disasters. Although there have been numerous hydrological studies on flood processes, most of these investigations were based on rainfall-type floods in plain areas. Few studies have examined high temporal resolution snowmelt floods in high-altitude mountainous areas. The Soil Water Assessment Tool (SWAT) model is a typical semi-distributed, hydrological model widely used in runoff and water quality simulations. The degree-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…The sequential uncertainty fitting (SUFI-2) program version 2 embedded in the SWATCUP software [47] was used for sensitivity analysis and model calibration. The T-states and p-values of the parameters were used before and after improving the statistical model to obtain parameter sensitivity [48,49]. The period from 1996 to1997 was chosen as the spin-up period, while calibration and validation periods were from 1998 to 2007 and 2008 to 2010, respectively.…”
Section: Hydrological Modelingmentioning
confidence: 99%
“…The sequential uncertainty fitting (SUFI-2) program version 2 embedded in the SWATCUP software [47] was used for sensitivity analysis and model calibration. The T-states and p-values of the parameters were used before and after improving the statistical model to obtain parameter sensitivity [48,49]. The period from 1996 to1997 was chosen as the spin-up period, while calibration and validation periods were from 1998 to 2007 and 2008 to 2010, respectively.…”
Section: Hydrological Modelingmentioning
confidence: 99%
“…Some physics-based hydrological models, such as SWAT [7][8][9], TOPMODEL/BTOP-MC [10,11], and MIKE SHE [12,13], have already been widely used to simulate the rainfall-runoff relationship for runoff prediction because of the definite and explainable mechanisms and the theoretically high accuracy of the modelling results, in addition to the user-friendly interfaces of the modelling software. However, the above-mentioned physics-based models usually require the observed rainfall as the input and the observed runoff data for calibration/validation and some additional data, like the digital elevation model (DEM), soil types, and land use information.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, the five most sensitive parameters of the donor catchment model are further localized in the target catchment model according to the new transferring rules (Section 3.3.5). A large number of studies have also shown that TLAPS, PLAPS, and SMFMX are highly correlated to catchment elevation [8,45,54]. CH_N2 is a coefficient that comprehensively reflects the influence of a rough river on the runoff.…”
Section: The Difference Of Model Parameter Transferability Methodsmentioning
confidence: 99%
“…The hydrological model is an essential tool to understand the hydrological process of catchments under the various climate input and land management [1], which includes a lumped conceptual model, and semi-distributed or distributed hydrological models, e.g., the Xin'anjiang model [2,3], the TOPMODEL model [4,5], and the SWAT model [6][7][8]. These models have to satisfy the accuracy requirements of the hydrological process's simulation with measurement flow data by parameter calibration and validation.…”
Section: Introductionmentioning
confidence: 99%